2002
DOI: 10.1128/jcm.40.12.4435-4438.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rpoB Mutations in Rifampin-Resistant Clinical Isolates of Mycobacterium tuberculosis from Turkey by DNA Sequencing and Line Probe Assay

Abstract: Mutations in an 81-bp region of the rpoB gene associated with rifampin resistance were studied in 41 rifampin-resistant clinical strains of Mycobacterium tuberculosis isolated in Turkey. Fourteen different rpoB alleles, three of which had not been reported before, were found. A reverse hybridization-based line probe assay (the Inno-LiPA Rif.TB test) for rapid detection of the mutations was evaluated with these isolates. Rifampin resistance was correctly identified in 23 of 41 isolates (56.1%) with the kit's R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
4
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 18 publications
11
86
4
2
Order By: Relevance
“…The mechanism of resistance to RIF involves missense mutations, small deletions or insertions in the rpoB gene encoding the b-subunit of RNA polymerase. Studies from diverse countries have shown that 95-96 % of all RIFresistant isolates have mutations within an 81 bp 'core region' of rpoB (Bártfai et al, 2001;Cavusoglu et al, 2002;Herrera et al, 2003;Mani et al, 2001;Telenti et al, 1993;Yue et al, 2003). In contrast, but perhaps not unexpectedly given its highly complex mechanism of action, the mutations causing INH resistance are located in more than three genes and regions (Barry et al, 1998;Slayden & Barry, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of resistance to RIF involves missense mutations, small deletions or insertions in the rpoB gene encoding the b-subunit of RNA polymerase. Studies from diverse countries have shown that 95-96 % of all RIFresistant isolates have mutations within an 81 bp 'core region' of rpoB (Bártfai et al, 2001;Cavusoglu et al, 2002;Herrera et al, 2003;Mani et al, 2001;Telenti et al, 1993;Yue et al, 2003). In contrast, but perhaps not unexpectedly given its highly complex mechanism of action, the mutations causing INH resistance are located in more than three genes and regions (Barry et al, 1998;Slayden & Barry, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the geographical distribution of the rpoB resistant alleles is essential for the development of diagnostic tools. Although sequence analysis of the rpoB gene has been shown to be effective for detecting RIF-resistance alleles in over 90% of RIF-resistant isolates from different geographical regions [6,7], there is only limited information from Sudan [8]. In order to find Sudanspecific mutations, that could potentially be used for the optimization of the current detection tools of RIF resistance alleles, we determined in this study the mutation profile occurring within an 81-bp fragment of the rpoB gene, in a collection of MDR clinical isolates of Mycobacterium tuberculosis isolated from Khartoum, Sudan.…”
Section: Multidrug-resistantmentioning
confidence: 99%
“…Mutations within the 81-bp hot-spot region (codons 507 to 533) account for more than 90% of RIF-resistant M. tuberculosis strains [6,7], but still there was a proportion of strains phenotypically RIFresistant but lacking mutation within the hot-spot region. Yue et al, 2003 [14] have reported that 10% of phenotypically RIF-resistant M. tuberculosis isolates did not show any mutations at the 81-bp region.…”
Section: Multidrug-resistantmentioning
confidence: 99%
“…La detección de MTBc por técni-cas moleculares es de gran utilidad porque ha permitido un diagnóstico más rápido respecto del cultivo y más sensible con respecto a la baciloscopia, desarrollándose en los últimos años, varias pruebas diagnósticas [7][8][9][10][11][12] . Una de estas es el ensayo Xpert ® MTB/RIF, que se realiza en el sistema GeneXpert ® (Cepheid, Sunnyvale, CA).…”
Section: Artículo Originalunclassified